Study on the effect of quercetine and lipoate on lipid peroxidation in the retina in experimental diabetes (Ukrainian Journal of Ophthalmology, 2026)
The experiment was performed on white rats and content of malondialdehyde and conjugated dienes in the retina and blood plasma in the condition of streptozotocine-induced diabetes development and quercetine and lipoate application was studied. In such conditions, the use of drugs studied significantly prevented an increase in temporary products of lipid peroxidation (LPO) in the retina and blood of streptozotocine-induced diabetic animals at all terms of diabetes development. The use of lipoic acid in a greater degree decreased the enrichment of final products of LPO in the retina and blood of streptozotocine-induced diabetic animals at all terms of diabetes development as compared to that when quercetine was used.
Keywords: streptozotocine-induced diabetes; retina; malondialdehyde; conjugated diene; experiment